Oscillating Realities: Hyperreality and Hegemony in Metamodernist Films - Belazouz, Asma (Social Empowerment Journal, 2025)
In an era marked by visual dominance, technological disruption, and political polarization, cinema transforms itself into a cultural critique that challenges the resulting social inequalities. Stylistic choices in cinema today reflect power dynamics through visuals and contribute to the portrayal of this reality. This paper examines how dominant cultural norms and illusions are reinforced within metamodernist films to influence the construction of reality. Drawing on critical theories of (hyper)reality and simulacra, the study analyzes a selection of films to explore how dominance is represented and negotiated, focusing on how directors employ metafictional devices to subvert illusions. By critically interrogating these aspects of power in metamodernist cinema, the paper sheds light on the intricate ways in which films engage with contemporary perceptions of existential themes such as identity and individuality.